Analyzing the Risk-return Relationship in Crude Oil Futures Market Using High-frequency Data. (December 2016) - Gong, Xu; Wen, Fenghua; Pan, Bin; Xia, Xiaohua
Abstract: We comprehensively examine the contemporaneous/intertemporal risk-return relationship in the crude oil futures market. Our empirical results, based on high-frequency transaction data, suggest the contemporaneous relation between risk (volatility risk, downside risk or jump risk) and return in the crude oil futures market is negative and statistically significant, and the contemporaneous negative relation between downside risk and return is stronger than two others. However, the intertemporal volatility/jump risk-return relationship is insignificant, and there is weak negative correlation between downside risk and excepted return in the crude oil futures market.